Analisis Sistem Pengendalian Internal dalam Peningkatan Kualitas Laporan Keuangan : (Studi Kasus di PT. Petrokimia Kayaku (Persero), Tbk Cabang Tanah Karo) - Adek Iskandar Siregar; Zuhrinal M Nawawi; Nur Fadhilah Ahmad Hsb (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to analyze the implementation of the internal control system at PT. Petrokimia Kayaku (Persero), Tbk Tanah Karo Branch, is aware of the suitability of the company's financial statements which have been presented based on PSAK No. standards. 1, and knowing the obstacles faced in implementing an internal control system. This research includes qualitative research with a qualitative descriptive analysis approach. The type of data used is primary data and secondary data which was carried out using interview and documentation techniques. The results of this research show that the company's internal control system is divided into two parts, namely financial audit and operational audit. However, in its implementation there are still several obstacles, namely audit results which are often ignored by company management, communication network problems between the Factory and head office, inadequate infrastructure to the Factory. Another obstacle at the head office is that the Head of SPI no longer has staff because the old staff have resigned so that SPI is not optimal in carrying out audits. Then the implementation of SOPs is not optimal. As well as obstacles in terms of human resource development, namely that the implementation of job training for employees is not carried out periodically so that employees are still constrained in carrying out their duties. In facing these obstacles, the company will always carry out continuous supervision and carry out training for all human resources at PT. Petrokimia Kayaku (Persero), Tbk Tanah Karo Branch so that the existing internal control system can run as well as possible.